Design Method for Concrete Mix Proportion Based on Indices of Strength and Durability of Concrete Exposed to Chloride Attack - Jiaqi Zhao; Wanting Sun; Tuo Shi; Chenghui Qin (Advances in Materials Science and Engineering)
In the current design code, concrete mix proportions are not based on durability parameters that can quantitatively design the requirement of service life for chloride-exposed structures. Multifactor calculation models of durability index are developed, and the replacement of mineral admixtures in concrete is determined according to predetermined concrete strength and durability requirements. The chloride diffusion coefficient and aging factor of concrete are chosen as index parameters for the resistance of concrete to chloride salts. A multifactor model of the chloride diffusion coefficient of concrete is then established by regression analysis based on the experimental data, and explicit expressions for the water-to-binder ratio and replacement of admixture were determined by solving the multivariate nonlinear equation system. By calculating the average compressive strength and chloride diffusion coefficient from their specified values, the mix proportion of concrete is determined. The superiority of the proposed method is demonstrated by the comparison with the current code. Lastly, an orthogonal experiment was conducted to demonstrate the validity of the proposed method for designing concrete mix proportions by referencing engineering practices. The results show that major parameters of concrete mix proportion can be determined quantitatively from structural design parameters such as compressive strength, chloride diffusion coefficient, and aging factor, satisfying the requirements of ultimate bearing capacity and service life for concrete structures in chloride environments, as demonstrated in this paper.